2013
DOI: 10.12973/ijese.2013.206a
|View full text |Cite
|
Sign up to set email alerts
|

The Persistence of Misconceptions about the Human Blood Circulatory System among Students in Different Grade Levels

Abstract: In this paper, it is aimed to investigate the persistence of misconceptions in the topic of the human blood circulatory system among students in different grade levels. For this reason, after discussions with biology educators, two tests consisting of open-ended questions were developed by the researcher and administered to students in four different grade levels. The first test was administered to 319 5th and 7th grade students in elementary school and the second one was administered to 400 1st and 4th year u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(18 citation statements)
references
References 25 publications
2
13
0
3
Order By: Relevance
“…Arnaudin and Mintzes (1985) similarly reported that about 40% of primary school children thought that the human heart is three-chambered (amphibian-type). A majority of children (55.9%) thought that the function of the heart is blood purification which is in agreement with other researchers (Arnaudin & Mintzes, 1985;Özgür, 2013;Özsevgeç, 2007).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Arnaudin and Mintzes (1985) similarly reported that about 40% of primary school children thought that the human heart is three-chambered (amphibian-type). A majority of children (55.9%) thought that the function of the heart is blood purification which is in agreement with other researchers (Arnaudin & Mintzes, 1985;Özgür, 2013;Özsevgeç, 2007).…”
Section: Discussionsupporting
confidence: 91%
“…Research on misconception is important because these incorrect understandings are strongly held and often very difficult to change (Mintzes & Wandersee, 1998;Özgür, 2013;Vosniadou, 2001). Thus, it is crucial to establish a valid method(s) to examine misconceptions in order to obtain the best picture about what children really know about biological phenomena.…”
Section: Problem Of Researchmentioning
confidence: 99%
“…This finding can be supported by the results of a body of research in the literature which asserted misconceptions in various populations [14,16,22]. In his study related to circulatory system in biology education, Özgür [40] identified that students thought clean blood circled in the left side of the body whereas dirty blood circled in the right side of the body. In the present study, several similar results were also obtained.…”
Section: Discussionmentioning
confidence: 76%
“…The heart's internal structure it is often depicted with three cavities (atriums or ventricles) instead of four (Arnaudin & Mintzes, 1985;Windschitl, 1995). The role of the heart is also misunderstood; students think that it produces or filters the blood (Ozgur, 2013). The circulatory system is regarded as a closed system; the amount of blood remains constant and the blood is moving in both directions inside the veins (Chi, Chiu & DeLeeuw, 1991).…”
Section: The Respiratory and The Circulatory Systems As Teaching/learmentioning
confidence: 99%